Informality as crisis management? – Work relationships in inter-municipal cooperation during the COVID-19 pandemic in Rhineland-Palatinate, Germany - Haße, Maximilian; Scharfenort, Nadine (ERDKUNDE, 2022)
Planning and networking are largely determined not only by existing regulations, but also by human relationships. Formal work relationships in professional contexts benefit in particular from informal communication, which in turn gives these work relationships a personal aspect. The COVID-19 pandemic and the resulting control measures were also challenging for work relationships, including those in planning contexts. A planning project in Germany, which forms the basis for this article, demonstrates this. Qualitative research was used to investigate the impact of the pandemic on project work and how the project participants dealt with the pandemic. Through comparative and retrospective observations of the cooperation over time, it was possible to identify participants’ strategies to continue work on the project. This analysis is based on 25 qualitative stakeholder interviews. The results show that the pandemic had varying impacts on the project’s networks. The strategic use of informal communication contributed significantly to the continuation of the project’s work, although this communication was used in different ways. In addition, for a long time, the project stakeholders were neither aware of the differentiation between formal and informal communication, nor of the relevance of informal communication. Analysing this understanding represents a central aspect of this article. In sum, strengthening informality in formal planning projects contributes to their success.